Endovascular management of HIV vasculopathy - Newcomer,Jack B.; Chishti,Emad A.; Raissi,Driss (Journal of Clinical Imaging Science)
HIV is a multisystem disease process that can affect the cardiovascular system resulting in vasculopathy. As highly active anti-retroviral therapy has allowed patients to live longer with the disease, vascular complications such as aneurysms, occlusive disease, spontaneous arteriovenous fistulae, and arterial dissections have been described. The pathogenesis of vascular-related complications in HIV is poorly understood but is thought to involve an interplay between viral-induced inflammation, vascular smooth muscle changes, endothelial alterations, and circulating blood factors. The most well-described management strategies for symptomatic aneurysm-related complications are surgical in nature, with mostly anecdotal reports of endovascular intervention. We present a case of a 24-year-old male who was found to have findings consistent with HIV vasculopathy on angiography after presenting with acute GI hemorrhage secondary to left gastric artery bleeding. Our patient was managed with endovascular embolization. Although studies have shown promise regarding the endovascular management of HIV-related aneurysmal complications in the short term, more research is needed to evaluate the long-term success of these interventions.